KAJIAN TINGKAT TUNGGAKAN KREDIT SUB SEKTOR PERKEBUNAN PADA BANK RAKYAT INDONESIA UNIT PASAR RENGAS KABUPATEN BATANGHARI PROPINSI JAMBI - Febrinarni, Febrinarni; Reflis, Reflis (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
This research is aimed at assessing the Agriculture Sector Loan Arrears in BRI unit Pasar Rengas District of Batanghari and to analyze their determinant factors. Respondents were purposively selected as many as 69 people that is 50% of 137 populations who applied for credit in the period from July to December 2009 to BRI unit Pasar Rengas District of Batanghari. Data were analysed using descriptive method while chi-square formula and the contingency coefficient formula are used to determine relationship between independent and dependent variables. The results of this study indicate that the level of customer credit arrears level at PT. BRI unit Pasar Rengas categorised as the high category, and the factors associated with the level of loan arrears are motivation, the number of family, loan experience, and revenue. Formal education and collaterals correlated significantly with the level of customer credit arrears.